Panulirus Species - Phillips, Bruce; Melville-Smith, Roy; Kay, M.; Vega-Velazquez, A. (John Wiley & Sons, Ltd, 2013)
Spiny lobsters are among the most valuable species in the world’s oceans. Because of this they have been a focus of research and several have become among the most studied exploited marine animals. Commercial fisheries exist wherever they occur and because they are generally shallow water species they have been subject to intensive fishing worldwide. The maintenance of the sustainability of the fisheries for spiny lobsters has seen wide - ranging research programs conducted over many years including studies of the biology and ecology of the lobsters and the environments and habitats in which they occur. This chapter concentrates on changes and developments in Panulirus lobster fisheries since 2006, as part of the ongoing quest for sustainable management of existing fisheries as well as increased production through enhancement and aquaculture. Important species including Panulirus cygnus, Panulirus argus, Panulirus interruptus and Panulirus ornatus are given special attention.